Seismic navigation data for Single-Channel Seismic (SCS) images from the Hudson Canyon and Western North Atlantic Ocean acquired during Conrad leg RC2101 (1977) (IEDA: Marine-Geo Digital Library, 2016)
This SCS seismic navigation data was collected in the Hudson Canyon area and Western North Atlantic Ocean during the Conrad leg RC2101 (1977) by investigator Charles Windisch. The files are in ASCII format.